How does Organizational Citizenship Behavior Influence The Service Quality of Bank Employees During The COVID-19 Pandemic? Evidence From in Bekasi, Indonesia - Siregar, Edison; Juniasti, Riwandari; Tobing, Fery (Golden Ratio of Human Resource Management, 2024)
This quantitative study investigates the relationship between organizational citizenship behavior (OCB) and service quality among 168 employees working in Bank Perkreditan Rakyat (BPR) establishments in East Bekasi, Indonesia. The research employs linear regression analysis to examine the extent to which OCB influences service quality within the context of BPRs. The sample was drawn from various BPRs in East Bekasi, utilizing structured surveys to collect data on employees' OCB and perceived service quality. The findings reveal a significant and positive relationship between organizational citizenship behavior and service quality. Specifically, employees who exhibit higher levels of OCB tend to contribute positively to the quality of services provided by BPRs. These results underscore the importance of fostering a culture of OCB within BPRs to enhance service quality and meet customer expectations effectively. The implications of this study extend to BPR managers and policymakers, highlighting the importance of promoting and incentivizing OCB among employees as a strategy for improving service quality and maintaining competitiveness in the financial services sector. Further research is recommended to explore additional factors that may influence the relationship between OCB and service quality and to validate the findings in different organizational contexts and geographical locations.